WORD FORMATION OF MESSAGING APPLICATIONS FOUND IN PLAY STORE - Giyatmi, Giyatmi; Arumi, Sihindun; Setiyono, Mas Sulis (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2021)
This study aims at describing the process of word formation used on messaging applications found in Play Store. This is a descriptive qualitative research. The data are messaging applications written in English and in the form of word. To collect the data, the researchers use observation. The analysis data consists of three steps namely data reduction, data display, and verification. There are 56 data found. There are 6 types of word formations; Affixation (4 data), compounding (15 data), blending (4 data), coinage (8 data), clipping (4 data), reduplication (1 data). However, there are 20 messaging application that cannot be classified into the type of word formation such as Path, Line, Lemon, etc. They are simple words that have already existed in English and have been used in everyday communication. Meanwhile, nowadays they are used as a name of messaging application and have the different meaning as the real meaning. The suffixes used in affixation process are –er, -ous, -ster. There are 6 formations of compounding used in the messaging application such as N+N, V+V, N+V, V+N, Adv. + Prep. There are 3 ways of blending process such as taking the whole part of the first word and taking the first syllable of the second, taking the first syllable of the first word and taking the whole part of the second word, taking two syllables from the front part of the first word and taking the last syllable of the second word. Coinage consists of name of company and name of product. There are two types of clipping found namely fore-clipping and back-clipping. Reduplication happens when there is a copying of the partial part of the word. Apparently, there are morphological processes used in life such as word formation to name the messaging application.